Why are productivity and wages higher in foreign firms? - Girma, Sourafel; Thompson, Steve; Wright, Peter W. (Economic & Social Studies, 2002)
This paper uses a panel data framework to examine whether foreign firms in the UK have higher levels of productivity and set higher wage rates than domestic ones ceteris paribus, or whether this is due to unmeasured characteristics. Its main finding is that foreign firms are more productive, by between 8 and 15 per cent, being particularly efficient in their use of capital. These advantages feed through into the wage levels of their employees, whose wages are higher as a result, effects that are particularly pronounced for firms from the United States.
Keywords: Productivity; Wages; UK; Quantitative methods; FDI; Foreign firms